Residual and Cumulative effect of Zinc on Yield, Quality of Soybean (Glycine max L.) and Various pools of Zinc in a Vertisol of Madhya Pradesh, cv. JS 97-52 - Raghuwanshi, Namrata; Sharma, B. L.; Uikey, Indu; Prajapati, Sunil (International Journal of Bio-resource and Stress Management, 2017)
The present field experiment was conducted during Kharif, 2014 at Department of Soil Science and Agricultural Chemistry, Jawaharlal Nehru Krishi Vishwa Vidhyalaya, Jabalpur (M.P.), its resulted that the each and alternate year Zn application significantly increased the plant height, pods plant-1, seeds pod-1, test weight, grain and straw yield, oil and protein content, Zn uptake by seed and straw, all Zn fractions and organic carbon content in soil after harvest of soybean over single year Zn application but each and alternate year Zn application were statistically at par. The application of 5 kg Zn ha-1 significantly increased the pods plant-1, seeds pod-1, test weight, grain and straw yield, oil and protein content, Zn uptake by seed, water soluble and occluded fraction and organic carbon in soil over control the highest plant height, nodules per plant, Zn content at different growth stages, total Zn uptake and available Zn content in soil were found at 10 kg Zn ha-1 which was at par with 5 kg Zn ha-1. The maximum content of water soluble and occluded fractions in soil was observed at 5 kg Zn ha-1, while exchangeable, complexed organically bound, residual and total Zn fraction was found maximum at 10 kg Zn ha-1.The water soluble, exchangeable, complexes, organically bound Zn fraction in soil has positively significant relationship with grain yield of soybean.